Daya Saing Calon Varietas Hibrida Nasa 29 di Jawa Timur - Bahtiar, Bahtiar; Azrai, Muhammad; Biba, M. Arsyad; Syakir, Muhammad (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
The research was conducted in Solokuro Village, Lamongan Regency, East Java, from September 2016 to January 2017. It aimed to know the competitiveness of advanced hybrid line of NASA 29. Genetically, the advanced hybrid line of NASA-29 has the superiority in the number of cob compare with the dominant varieties that planted by farmers.The result of the preliminary adaptation study indicated that the prolific charateristic reaches 70%, but in the Solokuro Village, Lamongan Regency just reach 10% due to drought stress at the beginning of growth, but the other superiority such as the size of cobs, good pollination and sturdiness stems are more superior then dominant existing varieties. Yield potential was equaled with several varieties such as DK-959 and BISI-2, even more than the varieties of PAC-339 and NK-33, so that NASA-29 is economically and profitably. Ratio revenue and cost of NASA-29 highest than other varieties. Then the farmers’ preferences on cob zise and yield potential of Nasa-29 are better than existing varieties. Therefore, NASA-29 has a prospect to developing in the future.